Temporary Measures on Bankruptcy: Alternatives to the Moratorium on Act 37/2004 in Resolving Indonesian Bankruptcy During the COVID-19 Pandemic - Ayu Permatasari, Cintya Sekar; Mellynda, Octa Nadia (Universitas Negeri Semarang, 2021)
The high number of bankruptcies in Indonesia, which increased to 54% in the pandemic era, had negative impacts on the economic ecosystem in Indonesia. A regulation is needed that can reduce the number of bankruptcies, in which the moratorium of Act 37/2004 is a discourse that will be predicted as the main solution. The moratorium of Act 37/2004 with its weaknesses has been rejected by many parties, so this research will offer a more appropriate alternative solution in the form of setting temporary measures on bankruptcy. This study seeks to describe the urgency and prospects of the presence of temporary measures on bankruptcy in Indonesia and recommend the regulation and implementation of temporary measures on bankruptcy in Indonesia. This legal research is normative legal research with data obtained from library research analyzed descriptive-qualitatively. The results of the study indicate that the moratorium of Act 37/2004 does not provide fair benefits for debtors and creditors in resolving bankruptcy problems so that it will actually hinder investment in Indonesia. Temporary measures on bankruptcy is an alternative that fills the absence of law in Indonesia regarding provision to bankruptcy relaxation. These measures provide fair benefits for both parties while still being able to file for bankruptcy but with a certain threshold and stimulus. Seeing the success of temporary measures on bankruptcy in various countries in reducing the number of bankruptcies, Indonesia needs to immediately implement the same thing in the Peraturan Pemerintah Pengganti Undang-Undang (PERPU).